Sagradas reescrituras: o evangelho segundo Eça de Queirós e Miguel Torga - Cruz, Renata Santos (2018)
This work presents a study of the presence of the biblical text in Portuguese short storieswhich were written in the 19th century by Eça de Queirós, and in the first half of the 20th century, by Miguel Torga. At first, this work aims to analyze short stories with an intertextual relationship with the Holy Bible, identifying the elements thatcompound these narratives. In addition, it seeks to identify the biblical tradition from the authors’perspective, observing the ratification or negation of the matrixial text. From this perspective, the following short stories were analyzed: O Suave Milagre (1898), Adão e Eva no paraíso (1897), A morte de Jesus (1894) and A aia (1893) by Eça de Queirós, and Vicente (1940), Jesus (1940), O regresso (1944), O leproso (1944) and Natal (1944), by Miguel Torga.